FILSAFAT SAINS SEBAGAI PERSPEKTIF TERHADAP PEMBELAJARAN FISIKA - Nabilah Az Zahra; Shafa Dwi Kamilah; Ulvia Khoirunisa Bisanti; I Ketut Mahardika; Ernasari; Sri Handono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This article explores the relationship between philosophy of science and physics learning. In line with the times, human life is experiencing very fast dynamics, so science is also experiencing development. The progress of time and technology is none other than due to the existence of science and the influence of scientific philosophy in human life. The history of physics and the philosophy of science are interdependent, meaning that philosophy can be truly understood if the reflection on the history of science has been previously understood. The aim of this research is to find out the philosophy of science as a perspective on physics learning as well as the relationship between the history of the philosophy of science. By teaching the history of physics, educators can provide information about how a physics concept was discovered. This type of research includes library research, namely research carried out in libraries and using reading materials in the form of books, journals and magazines. Revising thephilosophy of science based on ontology, epistemology and axiology as a basis for developing physics education can make a positive contribution to physics education. In addition, understanding the philosophy of science can encourage students' social interaction to solve problems.